OPINI DAN SIKAP SUBKULTUR PEMUDA ATAS ISU STUNTING DI DAERAH ALIRAN SUNGAI CITARUM - Jefri Audi Wempi; Chrisdina Chrisdina; Yolanda Stellarosa; Rizka Septiana; Dunola Tri Nugraeni (Jurnal Pustaka Komunikasi, 2023)
Human resource development is the focus of the government in the 2020-2024 National Medium Term Draft. One of the concerns is stunting. Bandung Regency is one of the areas with a high prevalence of stunting. Data from the 2022 Indonesia Nutrition Status Study shows that the prevalence of stunting in the Bandung Regency area reaches 31.1 percent or 112,000 people. Sukamulya Village is one of the villages that has implemented a stunting prevention program seriously. The stunting prevalence rate can be reduced to 11 percent per year in 2021 from 14 percent in 2019. This figure is indeed quite good, but the decline in the number which is only 1 percent per year is an interesting thing to study. One of the causes of stunting is early marriage by young people. Therefore this study aims to understand the opinions and attitudes of the youth subculture of Sukamulya Village on the issue of stunting. The theory used in this research is Youth Subculture and Social Learning Theory. The research methodology uses a constructivist qualitative approach. The results showed that the opinions and attitudes of the youth subculture in Sukamulya Village were divided into three groups. Groups that have awareness of the issues of stunting and early marriage, groups that know about stunting issues but don't care about them and groups that don't know. The emergence of these three groups is due to different levels of consciousness and intellect.